Impacto da utilização de pré-ênfase no desempenho sistêmico de um amplificador óptico paramétrico projetado para um guia de onda integrado de telurito - Pinto Neto, Pedro Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This work describes, by the use of simulations, the evaluation of performance of a two pump optical parametric amplifier (2P-OPA) designed on a tellurite waveguide using pre-emphasis power technique. The objective is to evaluate the application of the pre-emphasis power technique to minimize the power ripple at the output of the amplifier. The figures of merit used to compare the 2P-OPA performance without and with pre-emphasis are: the maximum bit error ratio (BER) achieved after each pass through the amplifier and the maximum optical span length that can be achieved when using this amplifier. The simulation software utilized is the VPItransmissionMaker™. The first setup analyzed is built to reproduce the results reported for 243 wavelength division multiplexing (WDM) signals quadrature phase shift keying (QPSK) modulated in single polarization with a 56 Gb/s bit rate for a -29 dBm input power per channel. The second setup includes the pre-emphasis onto the first setup with the addition of a block to unbalance the power signal. The pre-emphasis is made so the maximum power output per channel on the 2P-OPA is close to the average power output per channel (-10,47 dBm) when using the first setup. The BER of 13 channels, from the 243 transmitted channels, is estimated and compared to the case of the first setup. It's verified a decrease in the power variation of approximately 2,8 dB. Even with this decrease, the BER curves still have a similar behavior on both cases. Small BER variation is achieved because of the unbalancing of 3,5 dB used to make the power output per channel reasonably plane. The variation causes an increase of the maximum BER after the 12th amplifier. Consequently, this increase results in the reduction of the maximum optical span length from 1040 km to about 960 km. Unfortunately, this result do not support the use of pre-emphasis profile proposed

Neste trabalho é avaliado, com o uso de simulações, o desempenho de um amplificador óptico paramétrico de duplo bombeio (two pump optical parametric amplifier, 2P-OPA) projetado utilizando um guia de onda de telurito e usando pré-ênfase de potência. O objetivo do trabalho é avaliar a aplicação de pré-ênfase de potência visando reduzir as variações das potências de saída do amplificador. As figuras de mérito utilizadas para comparar os desempenhos do 2P-OPA com e sem o uso de pré-ênfase são: a maior taxa de erro de bit (bit error rate, BER) atingida após cada passagem pelo amplificador e o máximo comprimento de um enlace óptico que utiliza este amplificador. A montagem dos arranjos de simulação é feita utilizando o software VPItransmissionMaker™. O primeiro arranjo é montado para reproduzir os resultados encontrados na literatura para 243 canais usando multiplexação em comprimento de onda (wavelength division multiplexing, WDM) modulados em chaveamento por deslocamento de fase e quadratura (quadrature phase shift keying, QPSK) em polarização única com taxa de 56 Gb/s para uma potência de entrada próxima de -29 dBm por canal. Para a aplicação de pré-ênfase é adicionado um bloco a esse arranjo que será responsável por aplicar a desequalização de potência. A pré-ênfase é feita para que os canais na saída do 2P-OPA tenham a potência próxima ao valor médio de potência de saída (-10,47 dBm) obtido para o caso sem o uso da técnica estudada. A BER de 13 canais, entre os 243 canais transmitidos, é estimada e comparada ao caso em que não se utiliza a pré-ênfase. É verificada uma redução da variação de potência de aproximadamente 2,8 dB. Apesar da redução alcançada, as curvas de BER para ambos os casos mantêm um comportamento semelhante. Pequenas variações na BER são obtidas devido à desequalização de 3,5 dB aplicada para tornar a potência...
Impact of the use of pre-emphasis on the systemic performance of a parametric optical amplifier designed for an integrated waveguide of tellurium
Keywords: Amplificadores oticos; Comunicações oticas; Telecomunicações; Amplifiers, Optical; Communications, Optical; Telecommunication